Supply chain concentration and corporate green innovation: Evidence from China - Dan Qiao; Junzhen Jiao; Norlin Khalid; Mohd Helmi Ali (Innovation and Green Development)
With the rise of environmental awareness, stakeholders are increasingly insisting on a sustainable corporate strategy. This study examines the impact of supply chain concentration on green innovation in Chinese manufacturing firms listed on the A-share market from 2011 to 2022. The results show that increased supplier concentration hinders green innovation, while increased customer concentration facilitates it. Supplier concentration has a stronger dampening effect for firms with a high degree of brownwashing, a high degree of monopoly, a low degree of supplier stability and state ownership. The compensating effect of customer concentration is stronger for firms with a high degree of brownwashing, a low degree of monopoly, a high degree of supplier stability and non-state ownership. Further findings suggest that increased supplier concentration increases business risk and organizational redundancy within firms, thereby hindering green innovation. Increased customer concentration promotes green innovation by reducing bargaining power and easing financial constraints. This study provides empirical evidence that enhanced supply chain management promotes corporate green innovation.